Injury mortality report for São Paulo State, 2003 - Gawryszewski, Vilma Pinheiro (2007)
CONTEXT AND OBJECTIVE: Injuries are an important public health issue in the State of São Paulo. Each year around 32,000 people are killed and 180,000 are hospitalized due to injury. The aim of this work was to analyze fatal injury data to provide an overview on mortality due to injuries in the State of São Paulo in 2003, the most recent year for which data are available. DESIGN AND SETTING: Population-based descriptive study carried out in the State Health Department of São Paulo. METHODS: Data from 31,032 deaths due to injury were analyzed. The dataset was from the Mortality Information System (SIM/DATASUS). The data were stratified by sex, age, intent and mechanism of injury. Unadjusted and age and sex-specific rates were calculated per 100,000 population. RESULTS: The unadjusted injury mortality rate was 80.2/100,000 (140.2/100,000 for males and 22.4/100,000 for females). The highest rates were found for males and among young and old people. A greater proportion of intentional injuries than of unintentional deaths resulted in death (49.73% and 39.7%, respectively). Homicides were the leading cause, 44.6% overall (35.8/100,000), followed by motor vehicle traffic, 22.3% overall (17.9/100,000). Firearms played an important role among homicide deaths. Intention and mechanism of injuries varied according to sex and age group. CONCLUSION: These data indicate a need to develop injury prevention strategies, considering the magnitude of the problem and the groups at high risk. Homicides among young people have to be addressed. Motor vehicle traffic injuries play an important role for all ages.